Astragaloside IV/lncRNA-TUG1/TRAF5 signaling pathway participates in podocyte apoptosis of diabetic nephropathy rats - Lei, Xiao (Drug Des Devel Ther, 2018)
OBJECTIVE: This study aims to figure out the mechanism of astragaloside IV (AS-IV) in the protection of podocyte apoptosis in diabetic nephropathy (DN) rats. MATERIALS AND METHODS: Streptozotocin (STZ) was used to induce diabetes in rats, and the diabetic rats were treated with 5 mg/kg/d of AS-IV for 12 weeks. Albuminuria level, relative TUG1 and TRAF5 levels, and TRAF5 and cleaved-caspase-3 protein levels were examined by ELISA, quantitative reverse transcription (qRT)-PCR, and Western blot analyses, respectively. The interaction between TUG1 and TRAF5 was confirmed by RNA pull-down and RNA precipitation. TUNEL assay was used to detect podocyte apoptosis. RESULTS: Compared with control rats, DN rats had higher albuminuria and TRAF5 levels and lower TUG1 level. AS-IV treatment attenuated albuminuria and TRAF5 levels and improved TUG1 level in DN rats. TUG1 was downregulated and TRAF5 was upregulated in high-glucose-treated MPC5 cells, and AS-IV ameliorated the TUG1 level. In addition, TUG1 interacted with TRAF5, and TUG1 overexpression promoted degradation of TRAF5 protein. Besides, AS-IV modulated TRAF5 expression through regulating TUG1. AS-IV decreased podocyte apoptosis via the TUG1/TRAF5 pathway. Finally, in vivo experiment proved that si-TUG1 abrogated the protective effect of AS-IV on DN. CONCLUSION: AS-IV attenuated podocyte apoptosis and protected diabetic rats from DN via the lncRNA-TUG1/TRAF5 pathway.